Advancing the implementation of nature-based solutions in cities: A review of frameworks. Issue 125 (November 2021) - Wickenberg, Björn; McCormick, Kes; Olsson, Johanna Alkan
Abstract: Nature-based solutions (NBS) can help tackle climate change and advance urban sustainability by using nature to deliver social, ecological and economic benefits. However, their success largely depend on implementation for which several barriers exist. For NBS to be meaningful in terms of delivering positive impacts in cities, we need better understanding of how implementation is embedded in NBS frameworks. The aim of this paper is to i) understand how frameworks address implementation, and ii) extract and synthesize key elements and conditions required for enabling the implementation process. Taking a hermeneutic approach, the paper makes use of pre-understanding to interpret and analyse 'the whole' and 'the parts' of the implementation process and discuss how the discourse on NBS implementation could advance towards more operational understanding. This paper suggests that multi-stakeholder collaboration and co-creation of knowledge are important prerequisites for shared understanding of problems, developing actionable knowledge and adapting NBS to site-specific societal challenges. Advancing knowledge about the NBS implementation process is relevant for capacity building and governance of NBS at the local level and bridging policy areas, stakeholders and the knowledge needed to make NBS become relevant to broader society. However, more research is needed to i) move beyond conceptual propositions and towards operational understanding of NBS principles and ii) improve the understanding of how local collaboration and co-creation of knowledge can enhance capacity building and support implementation of NBS. Highlights: Few frameworks for NBS address implementation. Collaboration and co-development of knowledge are key elements in the NBS implementation process. The NBS concept must be integrated at different scales of urban planning. Future frameworks for NBS should address both experimentation and formal planning processes.